A multi-band high-efficiency envelope elimination and restoration CMOS power amplifier. (August 2020) - Mamdouh, Ahmed; Aboudina, Mohamed; Mohieldin, Ahmed N.; Hussien, Faisal
Abstract: A multi-band CMOS power amplifier has been realized to be used in high-efficiency handset applications. The proposed PA is based on class-E stage linearized using envelope elimination and restoration (EER) technique. In order to cover multiple frequency bands, a wide-band passive output matching network is designed and combined with band-select feature. This allows switching between two wide-band output matching networks; increasing frequency coverage and yet satisfying the criteria of high rejection of out-of-band emissions. A design methodology is introduced to optimize the values required for the wide-band passive network. The design has been implemented using CMOS 0.13 μm technology. Simulation results show frequency coverage from 800 MHz to 2.2 GHz with peak efficiency more than 60% (before taking the effect of supply modulator) and 47% after taking the losses of the supply modulator into account. The designed EER system achieves excellent linearity performance. The test and validation process includes LTE test signal with 16 QAM modulation scheme and signal bandwidth of 20 MHz.